El grupo de teatro “AQUELARRE” de la Universidad técnica de Cotopaxi como plataforma educomunicacional: audiencia y actores - Arias Coronel, Jonathan David (2020)
Nowadays, the theatre has become beyond just an art, linking it to educommunication and studying it as an educommunication platform is the result of the lack of studies in Ecuador and in the Province of Cotopaxi about both areas. Therefore, this research project aims to demonstrate that the Aquelarre Theatre Group of the Technical University of Cotopaxi has become an educommunication platform, it means it uses its position of alternative media of communication to educate through its acts. The methodological strategy had a qualitative approach through focus group techniques and surveys; the applied instruments were: a guide of 11 questions for the focus group and a questionnaire of 14 questions both elaborated according to the project´s objectives. These were directed to the actors of the group (focus group) and to students with seven and eight cycles of the Social Communication career (surveys). The research’s main results show that young people consider the Aquelarre group as an educommunication platform where they can receive education on several social, cultural, historical and environmental issues, among others. Also, its actors consider it as a tool to acquire communication skills such as expressiveness, good communication, retention, values, among others and academically, professionally and personally improvement. Among the main conclusions, the educommunicational value that the group´s acts have for audience stands out clearly, since they see it as an excellent platform to deal with difficult topics such as: sexuality, gender violence, bullying, drug addiction, among others.